Mysterium coniunctionis : an inquiry into the separation and synthesis of psychic opposites in alchemy /: an inquiry into the separation and synthesis of psychic opposites in alchemy. (2014) - Jung, C. G (Carl Gustav), 1875-1961
No abstract available